Benefit of Left Atrial Roof Linear Ablation in Paroxysmal Atrial Fibrillation: A Prospective, Randomized Study. Issue 5 (5th September 2014) - Arbelo, Elena; Guiu, Esther; Ramos, Pablo; Bisbal, Felipe; Borras, Roger; Andreu, David; Tolosana, José María; Berruezo, Antonio; Brugada, Josep; Mont, Lluís
Abstract : Background: Isolation of the pulmonary veins (PVs) for the treatment of atrial fibrillation (AF) is often supplemented with linear lesions within the left atrium (LA). However, there are conflicting data on the effects of creating a roof line (RL) joining the superior PVs in paroxysmal atrial fibrillation (PAF). Methods and Results: A cohort of 120 patients with drug‐refractory PAF referred for ablation were prospectively randomized into 2 strategies: (1) PV isolation in combination with RL ablation (LA roof ablation [LARA]‐1: 59 patients) or (2) PV isolation (LARA‐2: 61 patients). Follow‐up was performed at 1, 3, and 6 months after the procedure and every 6 months thereafter. After a 3‐month blanking period, recurrence was defined as the ocurrence of any atrial tachyarrhythmia lasting ≥30 seconds. PV isolation was achieved in 89% and complete RL block in 81%. RF duration, fluoroscopy, and procedural times were slightly, but not significantly, longer in the LARA‐1 group. After 15±10 months, there was no difference in the arrhythmia‐free survival after a single AF ablation procedure (LARA‐1: 59% vs. LARA‐2: 56% at 12 months; log rank P =0.77). The achievement of complete RL block did not influence the results. The incidence of LA macroreentrant tachycardias was 5.1% in the LARA‐1 group (n=3) versus 8.2% in the LARA‐2 (n=5) ( P =ns). Univariate analysis only identified AF duration as a covariate associated with arrhythmia recurrence (hazard ratio, 1.01 [95% confidence interval, 1.002 to 1.012]; P <0.01). Conclusion: The linear block at the LA roof is not associated with an improved clinical outcome compared with PV isolation alone. Clinical Trial Registration: URL: ClinicalTrials.gov. Unique identifier: NCT01203241.